The Conditions of the Mountains in the Verses of the Scenes of the Resurrection: Between Description and Simile - Hasan, Murad (Islamic Sciences Journal, 2023)
This study examines the linguistic depiction of mountains in the Doom’s day. The study, further, explores the continuity and the diversity of the rhetoric expressions and their relevance to the meaning they convey.